Masa Depan Faksionalisme Politik Golkar Pasca Orde Baru - Nurjaman, Asep (Faculty of Social and Political Sciences, Universitas Muhammadiyah Malang, 2018)
Since its inception, Golkar is a party that is carried by various functional groups with the aim of building political power to challenge the PKI. Since the reform era, Golkar has been abandoned by many of its support groups that have formed factionalism. The purpose of this study is to analyze the change of factionalism in the internal of Golkar in the post-New Order. The research method used is qualitative descriptive. The data used are secondary data derived from journals, books, and internet. The results show that: Golkar post-New Order experienced many changes in term of factionalism; factionalism that occurred during the New Order period stemmed from functional groups, while after the reforms became a factionalism based on personalism.